Pengembangan Sistem Kasir Berbasis Web menggunakan Model Prototype pada Usaha Laundry Indimo Azza untuk Meningkatkan Efisiensi Operasional dan Pelayanan - Satria Andikah Putra; Muhammad Agung Zikri; Januardy Ahda Setia Murad; Wasis Haryono (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The laundry business is rapidly growing in urban society, especially in areas with a high activity rate. One of the main challenges is the manual transaction recording process, which causes inefficiency and potential errors. This research aims to design and develop a web-based cashier system for Laundry Indimo Azza using the Prototype method. The system is designed to support customer data recording, automatic service fee calculation, service and employee management, and structured transaction and financial reporting. The Prototype method was chosen due to its ability to adapt to user needs through design and evaluation iterations. Testing results using white box and black box methods show that the system works according to expectations, increasing operational efficiency and speeding up customer service.